Media Art—XXI Century: Genesis, Art Programs, Education Problems International Scientific Conference / Международная научно-практическая конференция «Медиаискусство XXI век. Генезис, художественные программы, вопросы образования» - SAZIKOV ALEXEY V. / САЗИКОВ А.В.; EVALLYO VIOLETTA D. / ЭВАЛЛЬЁ В.Д. (Наука телевидения)
The article reviews the reports delivered on November 1–3, 2022, at the International Research-to-Practice Conference Media Art—XXI Century: Genesis, Art Programs, Education Problems. It was organized by the Russian Academy of Arts, the Research Institute of Theory and History of Fine Arts, the State Institute for Art Studies, Stroganov Moscow State Academy of Design and Applied Arts, the Moscow Architectural Institute (State Academy), and the National Academy of Design. The conference aimed at comprehending the current state of media art in the context of digitalization of classical works and methods of their exposure; at identifying key program and aesthetic dominants in media art; and at systematizing the most relevant educational projects. The organizers suggested the following aspects as the major research focuses: classical arts and media in digital discourse; new media in the socio-cultural environment; current media forms and their genesis; new media in the urban environment; interdisciplinary and authorial projects; educational processes and new competencies. Cultural institutions today are faced with the search for a definition of materiality, with fixation of transitory art; and in response, contemporary art studies are forced to develop new theoretical concepts to be used in scholarly discourse. It is how contemporary media, digital and post-digital technologies influence the state and development of contemporary art and art history practice, architecture, design, and decorative arts, that became the key research task of Media Art—XXI Century Conference. The conference demonstrated the wide range of aesthetic, art history, culturological and pedagogical aspects, which are incorporated in the creation, exposure, and further circulation of media art in the socio-cultural space. В статье представлен обзор докладов, озвученных в рамках Международной научно-практической конференции «Медиаискусство — XXI век. Генезис, художественные программы, вопросы образования» 1–3 ноября 2022, совместно организованной Российской академией художеств, НИИ теории и истории изобразительных искусств РАХ, Государственным институтом искусствознания, РГХПУ им. С.Г. Строганова, МАРХИ (Государственной академией) и Национальной академией дизайна. Целью конференции стало осмысление современного состояния медиаискусства в контексте цифровизации классических произведений и методов их экспонирования; выявление ключевых программных и эстетических доминант в сфере медиаискусства; систематизация наиболее релевантных образовательных проектов. В качестве ключевых исследовательских фокусов организаторами были предложены следующие ракурсы: классические искусства и медиа в цифровом дискурсе; новые медиа в социокультурной среде; актуальные формы медиа и их генезис; новые медиа в городской среде; междисциплинарные и авторские проекты; образовательные процессы и новые компетенции. Культурные институции сталкиваются сегодня с поиском определения материальности, с фиксацией искусства преходящего момента, в ответ современное знание вынуждено разрабатывать новые теоретические понятия для употребления в научном обиходе. То, как современные медиа, цифровые и постцифровые технологии влияют на состояние и развитие современного искусства и на искусствоведческую практику, на архитектуру, дизайн и декоративное искусство, стало ключевой исследовательской задачей настоящей конференции «Медиаискусство — XXI век. Генезис, художественные программы, вопросы образования». Результаты проведенного научного мероприятия продемонстрировали широту диапазона эстетических, искусствоведческих, культурологических, педагогических аспектов, заключенных в процессе создания, экспонирования и последующей циркуляции медиаискусства в социокультурном пространстве.